How to Create Together. AI-generated Images and Possible Intersections between Human and Artificial - Manchia , Valentina (E|C, 2024)
For some time now, artificial intelligence has been reappearing in media storytelling with its own agency. Good examples are AI art generators such as Dall-E, Stable Diffusion and Midjourney, which are capable of generating original images from text inputs: while some see these technologies as new prostheses for the human creative process, others see the danger of generative images undermining creativity itself, with painters, photographers and illustrators eventually being replaced by new machine subjects. In addition to reflecting on the nature of creativity, both human and synthetic, a topic on which the debate is still open, it seems interesting to us to look more closely at the different relationships between human and non-human subjects that these new devices enable, along with new forms of intersubjectivity and interobjectivity, as well as idiorrhythm as “mise en commun des distances” (Barthes). A privileged vantage point for exploring the possible intersections between human and non-human, and between “native” creativity and artificial generativity, is that of contemporary artistic experimentation, already aware of the pervasiveness of digital tools in image-making and increasingly interested in measuring itself against AI. Starting from an overview of media and artistic projects deal with generative technologies in various ways, this contribution aims to analyse AI image-generating devices in terms of the meaning effects they produce and the different regimes of the visible they imply, through the multiple balances between human and artificial they reveal.